Why Victims of Domestic Violence Still Survive Their Marriage? Preliminary Analysis of Forgiveness Dynamics Conditions - Afdal Afdal; Putri Fakhrina Sari; Miftahul Fikri; Ifdil Ifdil; Zadrian Ardi (Universitas Negeri Padang, 2019)
The purpose of this study was to find out how the dynamics of forgiveness of domestic violence victims. Anything that is the reason for the victim chooses to provide forgiveness and maintain the relationship of his household. The method used in this article is the library research method. The results of this study indicate that victims of domestic violence choose to provide forgiveness because it is influenced by certain factors. This factor becomes a force of the victim to maintain his household relationship. As for some of these factors, such as the presence of children, feeling ashamed to report the treatment of their husbands, not having a job so that they depend on living fully with their husbands and considering the length of marriage that has been fostered together.